Beyond Exercise: Sport-Based, Family-Centered, and Technology-Assisted Interventions Supporting Children with Autism Spectrum Disorder - Szopa, Piotr; Klamka, Antoni; Jóźwiak, Sabina; Szymczyk, Simone; Komoń, Aleksandra; Król, Kacper; Grobelny, Artur; Płusa, Aleksandra; Stodulska, Olga; Załuska, Urszula (Quality in Sport, 2026)
Background Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by deficits in social communication and restricted, repetitive behaviors. Its growing prevalence and functional burden have increased interest in non-pharmacological interventions, particularly physical activity and sport-based programs, as potential strategies to improve physical and neurobehavioral outcomes in pediatric populations. Aim This narrative review aimed to summarize current evidence on the effects of physical activity and exercise interventions on motor, cognitive, behavioral, and psychosocial outcomes in children and adolescents with ASD. Material and methods A narrative literature review was conducted using peer-reviewed studies on exercise-based interventions in pediatric ASD populations. Included were systematic reviews, meta-analyses, randomized controlled trials, and experimental studies assessing outcomes such as motor skills, executive functioning, social interaction, sleep, and behavioral regulation. Results Evidence indicates that structured physical activity may positively affect multiple domains in children with ASD. Exercise interventions were associated with improvements in motor skills, executive functions, and social abilities, along with reductions in behavioral problems and anxiety. Some studies also reported improved sleep and overall well-being. However, significant heterogeneity in intervention types, duration, and outcome measures was noted. Conclusions Physical activity is a valuable complementary element of multidisciplinary ASD management, supporting both physical health and neurobehavioral functioning. Further well-designed studies with standardized protocols and long-term follow-up are needed to determine optimal intervention strategies and their sustained effects.